What have we done to date? OSMARE: Organizational Structures for Smallholder Resilience - Organisational Structures for Smallholder Resilience (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
A summary of 2019 progress and lessons from the OSMARE project.